A new non regenerative gas absorbant catalyst for FCC unit - Ezani, Zahari (2010)
The FCC process operates in a dynamic heat balance with hot regenerated catalyst supplying the net heat demand required by the reaction system. Finely sized solid catalyst continuously circulates in a closed loop between the reaction system and the catalyst regeneration system. The feed and catalyst are intimately contacted in the riser reactor, in the proper ratio and with the proper residence time and temperature to achieve the desired level of conversion. The catalyst passes through a highly efficient,patented, spent catalyst stripper where any hydrocarbon product vapors entrained with the catalyst are removed and recovered. The process of cracking hydrocarbon provide human a fuel but the side effect is very dangerous to the environment because of releasing flue gases at regenerator. In this study, the non regenerate catalyst will be used in order to replace the current catalyst that need to be regenerate. This experiment was carried out in the reactor that has high test pressure so that it will stand still at high temperature. The catalyst was mixed with kerosene and burned at 190°C. The result obtained were test for it viscocity, density and funtional group. The catalyst funtional group is similar to the zeolite V which have been used in modern cracking process. The funtional group for product contain of several type of disturbance. The density obtained was 0.7461 g/cm3 and the viscosity obtained was 2.4 cP. The result showed that catalyst that had been used can crack down the hydrocarbon.